Analisis Trend Kinerja Keuangan PT Sumber Alfaria Trijaya Tbk menggunakan Rasio Profitabilitas dan Aktivitas Periode 2021-2024 - Trisnasari, Ni Ketut Ayu Citra; Pancawati, Ni Luh Putu Anom (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
This study examines the financial performance trends of PT Sumber Alfaria Trijaya Tbk for the period 2021-2024 using profitability ratios and activity ratios. This study uses a quantitative descriptive method with time series analysis on secondary data from the Indonesian Stock Exchange, analyzing how aggressive expansion strategies affect financial performance in the minimarket retail sector. The research result show a paradox, although the company demonstrated strong sales growth or an increase of 39.2% and asset utilization with a TATO ranging from 3,05-3,15 times and an inventory turnover of 9,70-10,62 times per year, profitability margins remained moderate with a stable GPM of 21-22% and an NPM decrease from 4% to 3%. ROA showed fluctuations between 10-13%, while ROE decreased from 30% to 23%, indicating that asset and equity growth outpaced profit growth. The declining trend of several ratios in 2024 indicates that the new outlets have not yet reached operational maturity. This research contributes to understanding the trade off between expansion strategies and short-term profitability in Indonesia’s competitive minimarket industry. However, the limitations of the research include the absence of competitor benchmarking, a short observation period, and reliance on quantitative financial data without qualitative strategic factors. Future research should integrate comparative analysis with competitors, extend the observation period, and use qualitative methods to provide comprehensive insights into the effectiveness of expansion strategies.